DISSIPATION KINETICS AND DIETARY RISK OF EMAMECTIN BENZOATE IN GRAPES USING LIQUID CHROMATOGRAPH-MASS SPECTROMETRY - BANKA KANDA KISHORE REDDY*, K. BHUVANESWARI, A. SUGANTHI, M. PARAMASIVAM and P. GEETHA, (The Journal of Research ANGRAU, 2021)
The study aim was to find out how emamectin benzoate disappears and is leaving terminal residuesin grapes. Modified QuEChERS method was developed, validated in Liquid Chromatograph-MassSpectrometry (LC-MS) and used for estimating the residues of emamectin benzoate. Themethod linearity was good (R2 > 0.99) and its Limit of Quantification (LOQ) was determined as 0.01mg/kg. Relative standard deviation (RSD) was found to be less than 5% for the average recoveriesobtained, ranged from 99.77 to 102.44 %. Emamectin benzoate half-life in grapes at single (11 g a.i/ha) dose (X) and double (22 g a.i/ha) dose (2X) was 1.11 and 1.22 days, respectively. The calculatedhazard quotient (HQ) was found evident and cause negligible risk in terms of health hazard to consumersdue to intake of emamectin benzoate residues through grapes at both studied doses.